THE E-COMMERCE POTENTIAL FOR HOME-BASED BUSINESSES: A CASE STUDY - Johanes Fernandes Andry; Julia Loisa (Fakultas Ilmu Komputer, 2016)
In Jakarta, the e-Business adoption has not only captured the interest of large organizations but has also been acknowledged and adopted by small, medium and micro sized enterprises. Mostly, these small and medium e-commerce-adopted companies are called Home-Based Business. The object of this research is a family home-based business which is adopted e-commerce system. The commonly used software development method is System Development Life Cycle (SDLC), and The Unified Modeling Language (UML) is generally accepted as the standard modeling notation for the analysis and design of the object that oriented on software systems. This research concludes that a web-based system can addressed the need of home-based business to expand the market scope by the internet penetration as one alternative to do the business expansion.